Asparaginase formulation impacts hypertriglyceridemia during therapy for acute lymphoblastic leukemia. Issue 1 (14th October 2019) - Finch, Emily R.; Smith, Colton A.; Yang, Wenjian; Liu, Yiwei; Kornegay, Nancy M.; Panetta, John C.; Crews, Kristine R.; Molinelli, Alejandro R.; Cheng, Cheng; Pei, Deqing; Ramsey, Laura B.; Karol, Seth E.; et al.
Abstract: Background: Glucocorticoids and asparaginase, used to treat acute lymphoblastic leukemia (ALL), can cause hypertriglyceridemia. We compared triglyceride levels, risk factors, and associated toxicities in two ALL trials at St. Jude Children's Research Hospital with identical glucocorticoid regimens, but different asparaginase formulations. In Total XV (TXV), native Escherichia coli l ‐asparaginase was front‐line therapy versus the pegylated formulation (PEG‐asparaginase) in Total XVI (TXVI). Procedure: Patients enrolled on TXV ( n  = 498) and TXVI ( n  = 598) were assigned to low‐risk (LR) or standard/high‐risk (SHR) treatment arms (ClinicalTrials.gov identifiers: NCT00137111 and NCT00549848). Triglycerides were measured four times and were evaluable in 925 patients (TXV: n  = 362; TXVI: n  = 563). The genetic contribution was assessed using a triglyceride polygenic risk score (triglyceride‐PRS). Osteonecrosis, thrombosis, and pancreatitis were prospectively graded. Results: The largest increase in triglycerides occurred in TXVI SHR patients treated with dexamethasone and PEG‐asparaginase (4.5‐fold increase; P  <1 × 10 −15 ). SHR patients treated with PEG‐asparaginase (TXVI) had more severe hypertriglyceridemia (>1000 mg/dL) compared to native l ‐asparaginase (TXV): 10.5% versus 5.5%, respectively ( P  = .007). At week 7, triglycerides did not increase with dexamethasone treatment alone (LR patients) but did increase with dexamethasone plus asparaginase (SHR patients). The variability in triglycerides explained by the triglyceride‐PRS was highest at baseline and declined with therapy. Hypertriglyceridemia was associated with osteonecrosis ( P  = .0006) and thrombosis ( P  = .005), but not pancreatitis ( P  = .4). Conclusion: Triglycerides were affected more by PEG‐asparaginase than native l ‐asparaginase, by asparaginase more than dexamethasone, and by drug effects more than genetics. It is not clear whether triglycerides contribute to thrombosis and osteonecrosis or are biomarkers of the toxicities.